Censurar para evitar el peligro: las censuras cinematográficas durante el franquismo, 1939-1959 - Fátima Gil Gascón (Ler História, 2021)
Film was not only one of the most popular forms of entertainment under Francoism. It was also one of the regime’s most important means of indoctrination, mainly thanks to the censorship that defined what Spaniards could and could not view. This article aims to analyze, through this censorship, the limits of what was accepted and acceptable to the Francoist society and observe the possible evolution of these limits and their relationship with social changes that occurred during the dictatorship. To this end, we will examine the role of the different methods of coercion that existed: Those exercised by official bodies and those created by the most reactionary clerical sector. Addressing what was forbidden, what was allowed and encouraged will allow us to define the limits of what was permissible and delve into Spanish society’s stance on issues such as morality and freedom. This article is part of the special theme section Film Censorship in the Iberian Dictatorships, guest-edited by Ana Bela Morais.